2022
DOI: 10.3389/fonc.2022.963925
|View full text |Cite
|
Sign up to set email alerts
|

Development of an ultrasound-based radiomics nomogram to preoperatively predict Ki-67 expression level in patients with breast cancer

Abstract: ObjectiveTo develop and validate a radiomics nomogram that could incorporate clinicopathological characteristics and ultrasound (US)-based radiomics signature to non-invasively predict Ki-67 expression level in patients with breast cancer (BC) preoperatively.MethodsA total of 328 breast lesions from 324 patients with BC who were pathologically confirmed in our hospital from June 2019 to October 2020 were included, and they were divided into high Ki-67 expression level group and low Ki-67 expression level group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
1
10
1
Order By: Relevance
“…Additionally, Cheng suggested that the edge characteristics of breast masses on ultrasound imaging can indirectly reflect the expression level of Ki‐67. Liu 32 developed a radiomics nomogram including maximum diameter of lesions, stiff rim sign, US‐reported ALN status, and radiomics signature to predict the expression level of Ki‐67, achieving AUC of 0.904 and 0.890 in the training and validation cohorts, respectively. These findings are consistent with our study, which found that for breast lesions with high expression of Ki‐67, Demetics paid more attention to the edge of the mass ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Cheng suggested that the edge characteristics of breast masses on ultrasound imaging can indirectly reflect the expression level of Ki‐67. Liu 32 developed a radiomics nomogram including maximum diameter of lesions, stiff rim sign, US‐reported ALN status, and radiomics signature to predict the expression level of Ki‐67, achieving AUC of 0.904 and 0.890 in the training and validation cohorts, respectively. These findings are consistent with our study, which found that for breast lesions with high expression of Ki‐67, Demetics paid more attention to the edge of the mass ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Feng, S et al extracted radiomics features from dynamic contrast-enhanced magnetic resonance imaging, and their radiomics models reached an AUC of 0.839 (95% con dence interval [CI], 0.768-0.895) within the training set and 0.795 (95% CI, 0.674-0.887) within the independent validation set in the prediction of Ki-67 status 20 . Liu et al constructed a radiomics model based on ultrasound images, and their results showed an AUC of 0.821 (95% CI:0.764-0.880) and 0.713 (95% CI:0.612-0.814) in the training and validation cohorts 21 . For our study, the metabolic information derived from PET/CT images were expressed as multiple radiomics features, which were used to predict the Ki67 status, and showed an AUC of 0.83[0.74 0.92] within the training set and 0.75[0.56 0.95] within the testing set.…”
Section: Discussionmentioning
confidence: 99%
“…These are then transformed into a high-dimensional dataset to be combined with the patient’s clinical information in the construction of a prediction model ( 14 ). Considerable progress has thus far been made in the differentiation of benign from malignant masses ( 5 , 6 ), the prediction of lymph node metastasis ( 15 , 16 ), the determination of molecular typing ( 17 , 18 ), and the evaluation of response to adjuvant chemotherapy ( 19 , 20 ). In addition to US, radiomics has also been used with magnetic resonance imaging (MRI) and X-rays in the development of various breast cancer predictive models, showing promising results in the noninvasive prediction of lesion malignancy ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%